STRATEGI PENINGKATAN KUALITAS PELAYANAN KEPARIWISATAAN DALAM UPAYA MENINGKATKAN JUMLAH WISATAWAN NUSANTARA DAN MANCANEGARA DI KOTA PALEMBANG - Edwar Juliartha (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
Review of the national constellation of tourism at this time could not be denied. that policy development in the field of tourism, particularly the development of local tourism sector remains a critical issue in the implementation of national development. In the report OECD Tourism Policy and International (1987) stated that, the success in the development of tourism will provide a positive impact on the three main things, namely